(untitled) (Research, Society and Development, 2020)
This article aims to describe and analyze articles about the teaching-learning process in the context of Technical Education for High School Level, in order to present the recent advances in the literature in the area and provide insights for the development of future research. It was oriented to meet the objective of the study through a bibliometric and content analysis, having as object of study the Brazilian academic production on the learning in the technical education integrated to the high school, in the period from 2015 to 2019. The survey of the articles analyzed was done through the CAPES platform and Google Scholar, with a total of 30 articles studied at the end. It was noticed that there is not an extensive literature dealing with the topic of learning in the scenario of Technical Vocational Education of Middle Level, moreover most of the articles were published more recently, (2018 and 2019). The results of the study also point out that there is no journal that stands out in the publications on this topic, as well as there is no author or reference institution in the publications, demonstrating that this is a topic that is still very dispersed among authors, journals and institutions. As for the content of the works and their respective research interests, studies on active learning methodologies and the use of information and communication technologies (ICT) in teaching-learning are highlighted.